Limitation of CIPAA implementation in the construction industry from contractor’s perspective in Klang Valley / Faris Hamizan Iskandar Zulkhairi ... [et al.] - Iskandar Zulkhairi, Faris Hamizan; Hussin, Siti Nurhayati; Saidin, Mohamad Tajudin; Yop Zain, Fairiz Miza; Hussein, Edelin (2021)
Construction Industry Payment and Adjudication Act (CIPAA) was introduced on 15 April 2014 to be used by the construction industry. Introduction of CIPAA is primarily to create a rapid and efficient mechanism for resolving disputes in construction contracts by implementing adjudicators' decisions and to provide a speedy and impartial solution to disputes arising in construction projects. However, it has been revealed that according to Asian International Arbitration Centre (AIAC), more than half adjudication cases are eventually being re-arbitrated and re-litigated, causing more delay in payment. This scenario creates an undesirable effect to the contracting parties involved in a construction project such as delay in the completion of the project, affecting the contractor’s reputation and reducing the profit margin of the project. Therefore, the objectives of this paper includes identifying the significant factors that contribute to payment problems, discovering the current implementation of CIPAA in addressing payment problems and investigating the limitations of CIPAA in settling disputes in the construction industry. A quantitative method of research is conducted using questionnaires as a tool for data collection. All data will be analyzed using the average index and presented in rankings. The respondents are proposed to be selected among G7 contractors in Klang Valley using purposive sampling method. The expected outcomes of this study include understanding factors that lead to payment issues, discovering the implementation of CIPAA in payment disputes and understanding CIPAA 's limitations in settling payment disputes. The findings of the research that help to facilitate the improvement of dispute settlement in Malaysia through statutory adjudication.